A damned Iowa greyhound : the Civil War letters of William Henry Harrison Clayton - Clayton, William Henry Harrison (University of Iowa Press, 1998)
William Henry Harrison Clayton was one of nearly 75,000 soldiers from Iowa to join the Union ranks during the Civil War. Possessing a high school education and superior penmanship, Clayton served as a company clerk in the 19th Infantry, witnessing battles in the Trans-Mississippi theater. His diary and his correspondence with his family in Van Buren County form a unique narrative of the day-to-day soldier life as well as an eyewitness account of critical battles and a prisoner-of-war camp. Clayton participated in the siege of Vicksburg and took part in operations against Mobile, but his writings are unique for the descriptions he gives of lesser-known but pivotal battles of the Civil War in the West. Fighting in the Battle of Prairie Grove, the 19th Infantry sustained the highest casualties of any federal regiment on the field. Clayton survived that battle with only minor injuries, but he was later captured at the Battle of Stirling's Plantation and served a period of ten months in captivity at Camp Ford, Texas. Clayton's writing reveals the complicated sympathies and prejudices prevalent among Union soldiers and civilians of that period in the country's history. He observes with great sadness the brutal effects of war on the South, sympathizing with the plight of refugees and lamenting the destruction of property. He excoriates draft evaders and Copperheads back home, conveying the intra-sectional acrimony wrought by civil war. Finally, his racist views toward blacks demonstrate a common but ironic attitude among Union soldiers whose efforts helped lead to the abolition of slavery in the United States.